Strategic Role of Artificial Intelligence in Reshaping Global Digital Marketing: Opportunities and Organizational Challenges - Abdul Robi Padri; Mar’atus Solikhah; Rudi Ferdiansah (Politeknik Siber Cerdika Internasional, 2025)
This study explores the strategic role of artificial intelligence (AI) in transforming digital marketing practices across global companies. In the era of rapid technological advancement, AI offers innovative tools that redefine customer engagement, campaign effectiveness, and market competitiveness. Employing a qualitative case study approach, the research gathered data through interviews with marketing executives, employee questionnaires, and direct observation of AI-driven marketing operations in ten multinational companies. The findings reveal that AI significantly enhances campaign personalization and efficiency, with 70% of respondents noting improved product relevance and 80% citing better marketing budget optimization. Despite these benefits, companies face persistent challenges, particularly in integrating systems and preparing employees. Data privacy concerns and the need to strike a balance between automation and creativity also emerged as critical issues. This study concludes that AI, while transformative, requires careful strategic implementation to maximize its potential in global marketing contexts. The study’s implications include guidance on training needs, strategic alignment, and ethical compliance in the adoption of AI.